2021
DOI: 10.1039/d1ra00193k
|View full text |Cite
|
Sign up to set email alerts
|

t-BuOK mediated oxidative coupling amination of 1,4-naphthoquinone and related 3-indolylnaphthoquinones with amines

Abstract: The 2-amino-1,4-naphthoquinones and 2-amino-3-indolylnaphthoquinones by the t-BuOK mediated oxidative coupling amination has been developed. The 2-amino-3-indolylnaphthoquinones were conducted further transformation to polycyclic N-heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…After that 1,4-naphthoquinone was regenerated by the aerobic oxidation of hydroquinone. [57][58][59][60] In this context, we were able to separate an intermediate 7 which was mentioned in the control experiment section. On the other hand, recently it has been shown that in the presence of hypervalent iodine (III) PIDA, thiophenol can generate sulfenium ion.…”
Section: Resultsmentioning
confidence: 92%
“…After that 1,4-naphthoquinone was regenerated by the aerobic oxidation of hydroquinone. [57][58][59][60] In this context, we were able to separate an intermediate 7 which was mentioned in the control experiment section. On the other hand, recently it has been shown that in the presence of hypervalent iodine (III) PIDA, thiophenol can generate sulfenium ion.…”
Section: Resultsmentioning
confidence: 92%
“…43, 160.56, 160.14, 158.32, 156.535 (CF, 1 J C,F = 227.3 Hz), 147.51, 142.08, 135.52, 135.29, 134.07, 131.39, 130.55, 126.38, 125.19, 125.07, 124.99, 123.04 (CF, 3 J C,F = 8.1 Hz), 116.18 (CF, 2 J C,F = 22.6 Hz), 115.80. 19 32, 155.42, 149.90, 141.56, 138.36, 135.10, 134.17, 131.54, 130.54, 129.36, 129.18, 128.53, 128.05, 126.45, 125.28, 124.21, 123.18, 97.67. HRMS: m/z calcd for C 22 H 15 Cl 2 N 2 O + (M + H) + : 393.0561; found: 393.0564.…”
Section: (E)-2-[(4-fluorophenyl)amino]-4-[(4-fluorophenyl)imino]naphthalen-1(4h)-one (3b)mentioning
confidence: 99%
“…05, 181.65, 148.77, 135.25, 133.65, 132.54, 130.84, 126.30, 125.75, 99.61, 37.09, 13.42. 19 Red solid; yield: 54.8 mg (85%); mp 167-169 °C.…”
Section: Y Dong Et Almentioning
confidence: 99%
“…Moreover, when 3aa and aniline (5a) were used as the substrates, 2-amino-3-indolylnaphthoquinone 6a was obtained in 85% isolated yield using t-BuOK (2 equiv) in DMF (2 mL) at room temperature for 2 h (Scheme 4b). 15 When 3aa and aniline (5a) were used with CoCl 2 (3 mol%), t-BuOK (1.5 equiv), and DMF (2 mL) at 120 °C for 24 h, the polycyclic N-heterocycle 7a was obtained in 86% isolated yield (Scheme 4c). 16 Polycyclic N-heterocycles are the key structural elements of natural products, drugs, and functional materials.…”
Section: Letter Synlettmentioning
confidence: 99%